2018
DOI: 10.1590/2318-0331.231820170153
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosedimentological modeling with SWAT using multi-site calibration in nested basins with reservoirs

Abstract: Calibration and validation of hydrosedimentological models, usually performed at the outlet of a single basin, does not always correctly represent the hydrosedimentological processes in the different subdivisions of dammed river systems. The aim of this study was to evaluate simple calibration techniques (watershed outlet) and multi-site calibration (watershed outlet and internal reservoirs) with the Soil and Water Assessment Tool - SWAT model, using two nested basins in the southern region of Brazil. Three mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…The decrease in the ESCO value from 0.95 to 0.36 allowed more water to be extracted from lower levels to meet the soil evaporative demands [49] and reduced the streamflow [50]. The GW_DELAY was reduced from 31 to 7.09, which would increase the baseflow in the model, also reported by Zanin et al [14] as the parameter adjusts the time water moves through the soil profile to the shallow aquifer recharge [49]. The CH_K2 value indicates the measure of the rate of water loss from the channel to groundwater [45].…”
Section: Sensitivitymentioning
confidence: 69%
See 2 more Smart Citations
“…The decrease in the ESCO value from 0.95 to 0.36 allowed more water to be extracted from lower levels to meet the soil evaporative demands [49] and reduced the streamflow [50]. The GW_DELAY was reduced from 31 to 7.09, which would increase the baseflow in the model, also reported by Zanin et al [14] as the parameter adjusts the time water moves through the soil profile to the shallow aquifer recharge [49]. The CH_K2 value indicates the measure of the rate of water loss from the channel to groundwater [45].…”
Section: Sensitivitymentioning
confidence: 69%
“…For the Navet hydrological model, it was found that the range of Res_K was 0.4 to 0.8. Noting that the soils at the Navet Reservoir can also be described as silty clay to clay [25], and for a soil texture reported as predominantly clayey/very clayey, it was found that Res_K was 0.30 [14] and that the calibrated values appear reasonable.…”
Section: Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…RCHRG DP has a range of 0 to 1, and lowering it reduces the fraction of percolation that fills deep aquifers. Percolated soil water replenishes more shallow aquifers in this situation, implying an increase in baseflow (Zanin et al, 2018).…”
Section: Sensitivity Analysismentioning
confidence: 97%
“…Although the majority of research in the literature focusing on SWAT model concludes that this model can satisfactorily estimate sediments (Duru et al, 2018), there are numerous studies on sediment modeling in which it was not possible to obtain satisfactory results (Zanin et al, 2018;Ferrigo, 2014;Strauch et al, 2013;Uzeika et al, 2012). We assume that the origin of the inconsistencies in the solid discharge simulations is due in part to the data that generated the sediment rating curve (daily sampling of solid suspended discharge -Qss, and flow measurement -Q), which presented a high dispersion along with the historical series.…”
Section: Calibration and Validationmentioning
confidence: 99%